Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 4844436 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Plantae", "Country is United States of America", "HasCoordinate is true" ] } The dataset includes 4844436 records from 271 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0021430-151016162008034/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences